Finland : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2002)
This 2002 Article IV Consultation highlights that the economic growth in Finland slowed sharply in 2001 in the face of a deteriorating external environment, but is expected to pick up significantly by 2003 after staying somewhat lackluster in 2002. The abrupt contraction of the information and communications technologies market, as well as a decline in traditional exports, contributed to a significant decline in both export volume growth and real growth overall in 2001. The main challenges for economic policy are interrelated to deal with high unemployment and the impact of a rapidly aging population.